A trama paradoxal no cuidado em saúde mental de crianças e adolescentes usuários de drogas - Martins, Michelle Ferreira (2017)
The recent implementation of Mental Health public policies aimed at children and adolescent users of alcohol and other substances and, consequently, the insertion of such clientele in psychosocial care services has generated impact and challenges in care. This research craved to understand how the Mental Health care for children and adolescent users of alcohol and drugs was being set up through Mental Health policies, the institutional history of a CAPSI and the subject’s plan. Psychoanalysis as theory and method guided us in this course. We have followed the path of legislation on child and juvenile Mental Health, the institutional history of a Child and Adolescent Psychosocial Care Center (CAPSI) and through the follow-up of a teenage drug user case assisted in that service. This psychoanalytic research also had the character of a clinical intervention, enabled by the follow-up of M.’s case and the daily routine of CAPSI. We used as a methodological resource a metapsychological field diary based on three axes: ethnological research, participant observation and clinical diary. The reading guided by the psychoanalytic listening and the instrumentalized transference allowed us to perform data analysis, set up a metapsychological essay and the construction of the clinical case. In that process, we perceived the presence of a repetitive and paradoxical motion between inclusion and exclusion, in a weave that involved politics, institutional history and the subject’s plan. Such dynamics directly influenced care practices in the psychosocial care of drug-addicted children and adolescents in the psychosocial network. Those children and adolescents had issues beyond their drug use, such as the presence of other mental health diagnosis and the lack of social and family support. They represented a socially marginalized group entangled in a paradoxal weave among inclusion and exclusion processes in which the drug became a resource to make them feel included from their exclusion condition. We also observe that a same movement occurred at other times in the institutional history with the insertion of different clientele of children and adolescents. We believe that such movement could help us rethink care practices and mobilize us to build a possible clinic in the daily care services for children and adolescents. We also propose, through the peripatetic clinic and psychoanalytic listening, a possibility of constructing care practices that value the specificities of childhood and adolescence, as well as the singularity of each and every subject in care.